Optical Properties and Surface Morphology of Thin Silver Films Deposited by Thermal Evaporation - 周明 李耀鹏 周晟 刘定权 (Chinese physics letters, 2015)
Thin silver films with different thicknesses are deposited by thermal evaporation, and the Drude-Lorentz mode is used to describe the optical properties of samples measured by an ellipsometer, and the thickness uniqueness analysis and reflection spectrum testing are used to verify the simulated results. We obtain the surface mor- phologies of the samples using the scanning electron microscopy, and calculate the relationship of reflectance with film thickness at wavelength 800 nm using the Mathcad software. Moreover, the effective medium approximation mode is used to explain the differences of wavelength-dependent n and k as the thickness changes. As the silver film thickness decreases, the optical constant changes regularly, and the films show flat surface, small cracks, discontinuous and island distribution, respectively, while n and k of the island distributed silver film have an intersection point in the visible spectrum. Our experiments provide an in-depth research for the ultra-thin silver film under thermal evaporation deposition, and will be helpful for its application in multilayers and plasmonic devices.